Urban Commuting and Daytime Population in Small Areas of a Metropolis:A Case Study of Brno, Czech Republic - Akkerman, Abraham; Kudrna, Jan; Apeltauer, Tomáš (Promet - Traffic&Transportation, 2012)
A simplified modelling approach to urban commuting patterns is achieved by focusing on daytime populations rather than on commuters, or on the commuting process itself. Whereas past studies were usually economic in nature, and viewed commuting as a process within the continuum of urban space and time, the approach addressing daytime populations transforms the modelling attempt into a demographic deliberation of a binary situation where switching of values between daytime and night-time indicators in each subarea throughout a metropolis is considered. The present study shows that such a focus on diurnal change as a binary concept offers a new paradigm in conceptualizing metropolitan commuting and transportation. Under certain assumptions, rooted in recent observations of metropolitan areas elsewhere, this study conjectures an analytic function for the estimation of daytime populations in small areas throughout the metropolitan region of Brno, Czech Republic. The conjectured relationship is a logistic function that utilizes as its independent variable the average household size in each of the subareas throughout the metropolitan region. Based on the data from the Czech census of 2001, the distributions of average household size and of residential populations throughout the metropolitan region are applied in a case study illustrating the utility of the proposed approach for the estimation of daytime populations throughout the region. The iterative procedure advanced here offers considerable potential for further applications elsewhere. KEY WORDS: metropolitan commuting, urban transportation, Brno, daytime population, average household size, logistic function, small area demography